Topochemical conversion of an imine- into a thiazole-linked covalent organic framework enabling real structure analysis - Haase, Frederik; Troschke, Erik; Savasci, Goekcen; Banerjee, Tanmay; Duppel, Viola; Doerfler, Susanne; Grundei, Martin M. J.; Burow, Asbjoern M.; Ochsenfeld, Christian; Kaskel, Stefan; Lotsch, Bettina V. (Nature Communications, 2018)
Stabilization of covalent organic frameworks (COFs) by post-synthetic locking strategies is a powerful tool to push the limits of COF utilization, which are imposed by the reversible COF linkage. Here we introduce a sulfur-assisted chemical conversion of a two-dimensional imine-linked COF into a thiazole-linked COF, with full retention of crystallinity and porosity. This post-synthetic modification entails significantly enhanced chemical and electron beam stability, enabling investigation of the real framework structure at a high level of detail. An in-depth study by electron diffraction and transmission electron microscopy reveals a myriad of previously unknown or unverified structural features such as grain boundaries and edge dislocations, which are likely generic to the in-plane structure of 2D COFs. The visualization of such real structural features is key to understand, design and control structure-property relationships in COFs, which can have major implications for adsorption, catalytic, and transport properties of such crystalline porous polymers.
CRIS-Team Scopus Importer:2022-04-14